Long-term effects of salt substitution on blood pressure in a rural North Chinese population - Zhou, B; Wang, H-L; Wang, W-L; Wu, X-M; Fu, L-Y; Shi, J-P (Journal of human hypertension, 2013)
Dietary sodium and potassium intake can influence blood pressure. The effects of salt substitution on patients with hypertension and normotensive family member controls, however, have not been evaluated in a rural Chinese population. The objective of this study, accordingly, was to assess the long-term effects of salt substitution on blood pressure. We conducted a double-blind, randomized controlled trial among 200 families in rural China to establish the 2-year effects of a reduced-sodium, high-potassium salt substitute (65% sodium chloride, 25% potassium chloride, 10% magnesium sulfate) compared with normal salt (100% sodium chloride) on blood pressure. Of the 462 individuals in the trial, 372 completed the study (81%). For normotensive subjects, the mean overall difference in systolic and diastolic blood pressure between the two groups at the 24-month follow-up was 2 mm Hg (95% confidence interval (CI) 0–4 mm Hg, P <0.05) and 2 mm Hg (95% CI 1–3 mm Hg, P <0.05), respectively. For subjects with hypertension, the mean overall decrease in systolic blood pressure showed a 4-mm Hg (95% CI 2–6 mm Hg, P <0.05) decrease between the two groups. Diastolic blood pressure was not affected by salt use in the hypertensive group. Salt substitution lowers systolic blood pressure in hypertensive patients and lowers both systolic and diastolic blood pressure in normotensive controls. Salt substitution, therefore, may be an effective adjuvant therapy for hypertensive patients and the potential efficacy in preventing hypertension in normotensive individuals.